2006
DOI: 10.1111/j.1945-5100.2006.tb00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and isotopic indicators of alteration in CR chondrites

Abstract: Molecular and isotopic indicators of alteration in CR chondritesRenazzo, Al Rais, and Y-790112 release qualitatively similar pyrolysis products, although there are some variations. Al Rais' macromolecular structure contains substantially higher relative abundances of alkylated and oxidized species and relatively lighter δ 15 N, suggesting that it has endured more extensive aqueous processing than the other CR chondrites. Renazzo appears relatively unprocessed, with a low degree of alkylation, a lack of detecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 71 publications
(154 reference statements)
3
13
0
Order By: Relevance
“…Murchison (CM2) has experienced more advanced aqueous alteration than EET 87770, but at similar temperatures (Clayton and Mayeda, 1984;Pearson et al, 2006). Type IIA chondrules in this meteorite contain glassy mesostasis that has undergone only partial alteration on the periphery of the chondrules, with the development of an alteration rim that is about 50 l in thickness where the glass is in contact with the fine-grained matrix.…”
Section: Aqueous and Thermal Alteration Of Individual Meteorites Basementioning
confidence: 96%
“…Murchison (CM2) has experienced more advanced aqueous alteration than EET 87770, but at similar temperatures (Clayton and Mayeda, 1984;Pearson et al, 2006). Type IIA chondrules in this meteorite contain glassy mesostasis that has undergone only partial alteration on the periphery of the chondrules, with the development of an alteration rim that is about 50 l in thickness where the glass is in contact with the fine-grained matrix.…”
Section: Aqueous and Thermal Alteration Of Individual Meteorites Basementioning
confidence: 96%
“…The table data were compiled from the literature (Alexander et al, 1998;Anders, 1988;Grady et al, 1988;Kerridge, 1985;Pearson et al, 2006;Robert and Epstein, 1982;Russell et al, 1996;Smith and Kaplan, 1970;Smith and Rigby, 1981;Swart et al, 1982;Yang and Epstein, 1983;Virag et al, 1989).…”
Section: Tablementioning
confidence: 99%
“…Chlorinated benzoic acids were found within Orgueil (CI1), Cold Bokkeveld (CM2), Murray (CM2), and Murchison (CM2), and data suggested that they may be present both free and bound to the macromolecular material (Schö ler et al, 2005). Polychlorinated (C 1 -C 4 ) biphenyls were detected in the pyrolysis products of Al Rais (CR2) and Yamato-790112 (CR2) (Pearson et al, 2006). A persistent concern in organohalogen studies of meteorites is the influence of halogenated solvents.…”
Section: Organohalogensmentioning
confidence: 99%
“…For detailed overviews of mineralogy, petrology, and composition of CR chondrites see Weisberg et al (1993), Kallemeyn et al (1994), Krot et al (2002), Pearson et al (2006), Abreu (2007), Weisberg and Huber (2007) and Schrader et al (2008). For the purpose of this study, we used a subset of CR chondrites, namely the CR2 chondrites: Renazzo and Al Rais and the GRO 95577 CR1 (see samples description below).…”
Section: Introductionmentioning
confidence: 99%